2016
DOI: 10.1163/15736121-12341318
|View full text |Cite
|
Sign up to set email alerts
|

Judgments of Religiosity following Minimal Interaction

Abstract: In the current study, unacquainted groups of both religious Christians and nonreligious atheists/agnostics rated themselves and each other on a number of attributes, including religiosity and morality. A Social Relations analysis revealed small, but statistically significant levels of consensus for impressions of religiosity. Subsequent correlations indicated that groups relied on the target's gender and race to reach consensus. Analyses of participants’ idiosyncratic ratings revealed similarity between religi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In addition to rating others’ IH (intellectually humble, intellectually arrogant*), participants also provided ratings for the Ten-Item Personality Inventory (Gosling, Rentfrow, & Swann, 2003), assessing (a) extraversion (extroverted/enthusiastic, reserved/quiet*), (b) agreeableness (sympathetic/warm, critical/quarrelsome*), (c) conscientiousness (dependable/self-disciplined, disorganized/careless*), (d) neuroticism (anxious/easily upset, calm/emotionally stable*), and (e) openness (open to new experiences/complex, conventional/uncreative*), as well as (f) leadership (a good leader, prefers to follow others*, good at helping people work together), (g) self-esteem (has high self-esteem, self-confident, has a low opinion of him-/herself*), and (h) intelligence (intelligent, competent). These additional traits have been used in previous round-robin designs (e.g., Meagher, 2016; Meagher & Kenny, 2013; Meagher et al, 2015) and, if statistically significant target variance is found for IH, can be used to assess what other judgments covary with the groups’ consensus for IH.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to rating others’ IH (intellectually humble, intellectually arrogant*), participants also provided ratings for the Ten-Item Personality Inventory (Gosling, Rentfrow, & Swann, 2003), assessing (a) extraversion (extroverted/enthusiastic, reserved/quiet*), (b) agreeableness (sympathetic/warm, critical/quarrelsome*), (c) conscientiousness (dependable/self-disciplined, disorganized/careless*), (d) neuroticism (anxious/easily upset, calm/emotionally stable*), and (e) openness (open to new experiences/complex, conventional/uncreative*), as well as (f) leadership (a good leader, prefers to follow others*, good at helping people work together), (g) self-esteem (has high self-esteem, self-confident, has a low opinion of him-/herself*), and (h) intelligence (intelligent, competent). These additional traits have been used in previous round-robin designs (e.g., Meagher, 2016; Meagher & Kenny, 2013; Meagher et al, 2015) and, if statistically significant target variance is found for IH, can be used to assess what other judgments covary with the groups’ consensus for IH.…”
Section: Methodsmentioning
confidence: 99%